(untitled) (IAHS Medical Journal, 2024)
Background: Noise, inappropriate temperature, insufficient light, overcrowded classes, misplaced boards and inappropriate classroom layout all could be confounding variables distracting students in class. The objective of the study to emphasizes on the effects of classroom noise on student’s learning performance, students’ perception on noise, internal and external noise levels. Materials and methods: This cross sectional study was conducted from January to December 2018 to assess any relationship between environmental noise level and learning performance of secondary school students, evaluation of various noise descriptors such as L10, L50, L90, Leq, and NC was measured with a smartphone using calibrated sound level meter app. The population of the study included students from class seven to class ten of the academic year 2017-2018 in Dhaka, of whom 580 students from three schools were selected by systematic random sampling. Results: Among the participants 66.6% were male and the rest 33.4% were female aging from 13 to 16 years. In school-2, students of class seven were exposed by highest level of sound 81.08 dB and lowest level was 73.55 dB in class eight classroom. In school-1, highest level of sound was 77.69 dB in class seven and lowest level was 75.99 dB in class nine. In school-3, highest level of sound was measured 78.72 dB in class eight and lowest level was 75.03 dB in class nine. Conclusion: Younger secondary school children appear to be more affected by noise than older students IAHS Medical Journal Vol 6(1), June 2023; 53-57